2010
DOI: 10.1515/cclm.2010.238
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Nova StatSensor whole blood point-of-care creatinine analyzer for the measurement of kidney function in screening for chronic kidney disease

Abstract: Isotope dilution mass spectrometry alignment of the StatSensor will identify most patients with estimated glomerular filtration rate <60 mL/min, but there will be many falsely low estimated glomerular filtration rate results that require laboratory validation. Creatinine results need improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(70 citation statements)
references
References 17 publications
6
63
1
Order By: Relevance
“…It has previously been reported that the STA analyzer was highly sensitive in determining whether renal function was normal or impaired and that without adjustment, it may underestimate sCr levels (9,14). The present study demonstrates that it overestimates sCr with and without adjustment.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…It has previously been reported that the STA analyzer was highly sensitive in determining whether renal function was normal or impaired and that without adjustment, it may underestimate sCr levels (9,14). The present study demonstrates that it overestimates sCr with and without adjustment.…”
Section: Discussionsupporting
confidence: 54%
“…1), measures the sCr levels in blood samples in 30 sec. It is used to screen for chronic kidney disease (CKD) (9), adjusting doses of potentially toxic renal drugs whose administration requires renal function monitoring (10) and to monitor kidney transplant recipients (11). The instrument is also used for evaluating renal function in radiology suites (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Participants identified as at risk of CKD moved to step 2, where clinical measurements, including point-of-care creatinine testing (Stat Sensor) and urinalysis, were obtained. The StatSensor tool has demonstrated good sensitivity (96%) and moderate specificity (79%) for detecting CKD, and has been suggested for use in screening of CKD (13)(14)(15)(16). However, the single random urine dipstick measurement does not capture albuminuria, and thus CKD was defined using a single creatinine measurement.…”
Section: Overview Of the Seekd Screening Programmentioning
confidence: 99%
“…6 Regarding acceptability, 99% found it convenient, and 96% felt immediate results and feedback helped them understand their condition.…”
Section: Impact Compared With Existing Technologymentioning
confidence: 99%
“…PrevIous reseArCh Accuracy compared with existing technology Most studies found creatinine POC devices to be reliable alternatives to laboratory testing; however, some noted a tendency of devices to underestimate renal impairment, [4][5][6] as well as poor inter-device concordance. 7 A study comparing creatinine levels from two Nova StatSensor™ devices against laboratory values in 401 consecutive patients undergoing contrast CT scans showed that correlation between the two POC devices differed between the two study centres (mean r = 0.93, P<0.0001; versus mean r = 0.84, P<0.0001).…”
mentioning
confidence: 99%